Algae-Mediated Removal of Prevalent Genotoxic Antibiotics: Molecular Perspective on Algae-Bacteria Consortia and Bioreactor-Based Strategies - Wani, Atif Khurshid; ul Gani Mir, Tahir; Akhtar, Nahid; Chopra, Chirag; Bashir, Showkeen Muzamil; Hassan, Shabir; Kumar, Vineet; Singh, Reena; Américo-Pinheiro, Juliana Heloisa Pinê [UNESP] (Springer Nature, 2024)
Antibiotic pollution poses a potential risk of genotoxicity, as antibiotics released into the environment can induce DNA damage and mutagenesis in various organisms. This pollution, stemming from pharmaceutical manufacturing, agriculture, and improper disposal, can disrupt aquatic ecosystems and potentially impact human health through the consumption of contaminated water and food. The removal of genotoxic antibiotics using algae-mediated approaches has gained considerable attention due to its potential for mitigating the environmental and health risks associated with these compounds. The paper provides an in-depth examination of the molecular aspects concerning algae and bioreactor-driven methodologies utilized for the elimination of deleterious antibiotics. The molecular analysis encompasses diverse facets, encompassing the discernment and profiling of algae species proficient in antibiotic degradation, the explication of enzymatic degradation pathways, and the refinement of bioreactor configurations to augment removal efficacy. Emphasizing the significance of investigating algal approaches for mitigating antibiotic pollution, this paper underscores their potential as a sustainable solution, safeguarding both the environment and human health.